Locus of Control dan Variabel Demografi sebagai Faktor Penentu Resiliensi Trauma: Studi pada Wanita Muda yang Pernah Terpapar Kekerasan - Alfina Rizkia; Chandradewi Kusristanti (Jurnal Ilmu Perilaku, 2020)
The number of violent incidents on women is increasing every year in Indonesia. Some women can survive through traumatic experiences, and it is related to their resilience. Locus of control (LoC) is known to contribute to resilience by enhancing individuals’ self- control and problem-solving behavior. This study aims to determine the role of LoC in trauma resilience among 134 young women (20 – 40 years old) who were exposed to violence (domestic, physical, and sexual) and a minimum of high school education. This study used a quantitative approach with the Locus of Control Scale (α = 0.732, 18 items) and the Trauma Resilience Scale (α = 0.961, 48 items). Two hypotheses are proved in this study: (1) external LoC significantly contributes to trauma resilience (p = .000, R2 = .139), (2) there is a significant difference between violence exposure (<.001), perpetrators (.005), and disclosure to others about their experience of violence (.009). We also found that no participants reported a dominant internal LoC, so future studies are advised to focus on women who were exposed to violence with a more dominant internal LoC.